2018
DOI: 10.1007/s00423-018-1688-8
|View full text |Cite
|
Sign up to set email alerts
|

Is systematic nasogastric decompression after pancreaticoduodenectomy really necessary?

Abstract: The absence of systematic nasogastric decompression after PD might reduce postoperative complications, DGE, and LOS. These encouraging results deserve to be confirmed by a prospective randomized study (NCT: 02594956).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 43 publications
3
29
0
3
Order By: Relevance
“…In addition, one study was excluded because some patients in the NGD group underwent nasogastric tube insertion (NGT) [20]. Finally, six studies were included in the systematic review and meta-analysis [5,15,16,[21][22][23]. The final analysis included a total 940 patients, with 484 patients in the RGD group, and 456 patients in the NGD group.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, one study was excluded because some patients in the NGD group underwent nasogastric tube insertion (NGT) [20]. Finally, six studies were included in the systematic review and meta-analysis [5,15,16,[21][22][23]. The final analysis included a total 940 patients, with 484 patients in the RGD group, and 456 patients in the NGD group.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported on postoperative complications [15,16,[21][22][23]. Overall complications were defined and graded using the following: Common Terminology Criteria for Adverse Events CTCAE (v4.0) (Grade 1-5) [22]; the international Clavien-Dindo grading system [24]; the 5-grade scale described by DeOliveira et al [24].…”
Section: Primary Outcomes Overall Complicationsmentioning
confidence: 99%
See 3 more Smart Citations